KARAKTERISTIK BUAH NANGKA (Artocarpus heterophyllus Lamk) SIAP SAJI YANG DIPASARKAN DI KOTA PALU - Anggriana, Anna; Muhardi, Muhardi; Rostiati, Rostiati (AGROTEKBIS, 2017)
The purpose of this study was to determine the physical, chemical characteristic and organoleptic of jack fruit fast food which marketed in Palu city. This study used a Randomized Block Design (RBD) consisting of 4 locations selling of jack fruit in Palu city and each locations is represented by 4 seller as a group. So there are 16 experimental units. The parameter consisted of flavor, texture, color, taste, fresh weight of fruit and water content. Analysis of the data using another test, if there are significant differences between the result of the analyze then tested by using advanced testing Honestly Significant Different (HSD) of 5% level. The result showed that location selling of jack fruit influential real toward flavor, texture, color, and taste, but nothing influential real toward fresh eight and water content.Â Key Words : Characteristic, Jack fruit.